Cities in a Pandemic: Evidence from China - Badi H. Baltagi; Ying Deng; Jing Li; Zhenlin Yang (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the impact of urban density, city government efficiency, and medical resources on COVID-19 infection and death outcomes in China. We adopt a simultaneous spatial dynamic panel data model to account for (i) the simultaneity of infection and death outcomes, (ii) the spatial pattern of the transmission, (iii) the inter-temporal dynamics of the disease, and (iv) the unobserved city- and time-specific effects. We find that, while population density increases the level of infections, government efficiency significantly mitigates the negative impact of urban density. We also find that the availability of medical resources improves public health outcomes conditional on lagged infections. Moreover, there exists significant heterogeneity at different phases of the epidemiological cycle.
Keywords: R10; R50; I18; 330; Covid-19; urban density; government efficiency; cities